Diskursus Diskursus Janda Manado: Antara Sosio-Teologis dan Ekofeminisme - Stevanus, Alexander (Sekolah Tinggi Teologi Parakletos Tomohon, 2024)
Abstract: The status of widow is always associated with a negative stigma, especially for young widows or flower widows. Widow status is a status obtained due to divorce due to death (divorce) and divorce due to family problems or conflicts. Widow status carries a burden both emotionally and socially, especially for widows in the Manado context who experience social status discrimination. Janda Manado was formed due to the local popular cultural context of Manado and the influence of foreign cultural fashion. Manado widows are no longer seen as women in social status, but as social bodies that are seen only as sexual bodies. The aim of this research is to provide a critical analysis of socio-theological and ecofeminism. The research method used is research with a qualitative approach. The results of this research found that the Bible provides a clear theological basis for the socio-theological and ecofeminist analysis of the Manado widow context. In the text Exodus 22: 22 it is stated: